Interaction between hunting strategy, habitat type and stratum drive intraguild predation and cannibalism - Michalko, Radek; Michalko, Radek; Birkhofer, Klaus; Pekár, Stano (Dryad, 2021)
Intraguild predation (IGP) is a common interaction between generalist
predators when they competitively exploit similar resources and prey on
each other. Theoretical models predict limitations for intraguild predator
coexistence unless some mechanisms, such as utilization of alternative
prey (i.e., trophic niche partitioning) and cannibalism, increase the
relative intraspecific clustering and interspecific segregation. As
hunting strategies determine trophic niches of predators and their own
vulnerability to predation, the hunting strategies may also determine the
relative importance of cannibalism, predation, and exploitative
competition and consequently the intensity of IGP. The importance of
hunting strategies on the potential outcome of IGP and how habitat
properties modify the interaction between hunting strategies remain poorly
understood. Using published data on spider prey of spider predators, we
first investigated how predation of a top-predator on a mesopredator is
determined by the functional distance between both predators to understand
how predation and exploitation are distributed in spider communities.
Subsequently, we investigated the predation among spiders with particular
hunting strategies to understand which strategies interact most
frequently. We also investigated whether the interaction between hunting
strategies was influenced by habitat type (forest, open (semi)natural
habitat, agroecosystem) or by habitat stratum (ground vs. vegetation). The
hunting strategies of top-predators and mesopredators interacted to
determine the relative capture proportions of conspecifics and
hetero-specifics. This interaction was further modified by habitat type
and stratum. Two mechanisms can reinforce coexistence in highly diverse
spider communities. First, top-predators preyed most frequently on
functionally distinct mesopredators, which indicates the overall intensity
of IGP may be relaxed by a balanced distribution between exploitative
competition and predation. Second, cannibalism was common for
top-predators with a hunting strategy of frequently preying on
functionally similar mesopredators. Cannibalism may lead to
self-limitation of top-predator populations and may thereby facilitate
coexistence between two predator species.
Keywords: coexistence; functional trait; Land-use change; niche; spider